Comparative study on some egg quality traits among four close-bred stocks of Japanese quail - Ahmad, S. (Scientific Journal of Zoology, 2013)
Present study wasconducted to evaluate some egg quality traits among four close-bred stocks(CBS) of Japanese quail at Avian Research and Training (ART) Centre, Universityof Veterinary and Animal Sciences, Lahore, Pakistan. For this, a total of 144quail eggs having 36 eggs of each CBS (Major, Kaleem, Saadat and Zahid) weresubjected to egg quality analysis. Data were recorded regarding egg weight (g),yolk index %, Haugh Unit and shell thickness (mm). Statistical analysis of dataaccording to Completely Randomized Design through one-way ANOVA technique andcomparison of mean using Duncan’s Multiple Range test revealed significantdifferent among four CBS. Significantly higher Egg weight (g) and shellthickness (mm) was observed in CBS M as compared to K, S and Z. Better Haughunit score was found in CBS Z as compared to rest of CBS. However, nosignificant effect of CBS on yolk index was also observed. It is concluded thatfour CBS of Japanese quail had significant effect on egg weight, shellthickness and Haugh unit score except yolk index.